Improved Rotor Speed Brushless DC Motor Using Fuzzy Controller - Jafar Mostafapour; Jafar Reshadat; Murtaza Farsadi (IAES Indonesian Section, 2015)
A brushless DC (BLDC) Motors have advantages over brushed, Direct current (DC) Motors and , Induction motor (IM). They have better speed verses torque characteristics, high dynamic response, high efficiency, long operating life, noiseless operation, higher speed ranges, and rugged construction. Also, torque delivered to motor size is higher, making it useful in application where space and weight are critical factors. With these advantages BLDC motors find wide spread application in automotive appliance, aerospace medical, and instrumentation and automation industries This paper can be seen as fuzzy controllers compared to PI control BLDC motor rotor speed has improved significantly and beter result can be achieve.